2014
DOI: 10.1039/c3ra44723e
|View full text |Cite
|
Sign up to set email alerts
|

Large area, flexible ordered mesoporous carbon films from soft templating on polymer substrates

Abstract: Mesoporous carbon films are generally fabricated on rigid substrates that act to provide mechanical stability. Here, instead of utilizing rigid substrates, a thin sheet of polyimide (Kapton) is utilized as the substrate to enable continuous production of sheets of soft templated mesoporous carbon films. The mesoporous carbon film is well adhered to the carbonized Kapton. Although mesoporous carbon is generally considered brittle, carbonization of the coated polyimide yields a tough flexible sheet that can be g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…2 Another strategy is to use a block copolymer (BCP) as a template to produce carbon nanostructures aer pyrolysis at elevated temperatures, as self-assembly of a block copolymer offers access to ordered nanodomains with tunable dimension and structure through control of such molecular parameters as volume fraction and molecular mass. [5][6][7][8][9][10][11][12][13][14][15][16] Several literature reports describe small organic molecules as sources of carbon within BCP self-assembled templates that yield carbon nanostructures of all dimensionalities. [5][6][7][8][9][10][11][12][13][14][15][16] As BCP materials act only as templates, removal of these templates is necessary aer pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Another strategy is to use a block copolymer (BCP) as a template to produce carbon nanostructures aer pyrolysis at elevated temperatures, as self-assembly of a block copolymer offers access to ordered nanodomains with tunable dimension and structure through control of such molecular parameters as volume fraction and molecular mass. [5][6][7][8][9][10][11][12][13][14][15][16] Several literature reports describe small organic molecules as sources of carbon within BCP self-assembled templates that yield carbon nanostructures of all dimensionalities. [5][6][7][8][9][10][11][12][13][14][15][16] As BCP materials act only as templates, removal of these templates is necessary aer pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Several literature reports describe small organic molecules as sources of carbon within BCP self-assembled templates that yield carbon nanostructures of all dimensionalities. [5][6][7][8][9][10][11][12][13][14][15][16] As BCP materials act only as templates, removal of these templates is necessary aer pyrolysis. Recent reports have demonstrated that cross-linked self-assembled BCP can be pyrolyzed directly into carbon nanostructures with morphological delity without addition of small organic precursors, as BCP itself is an organic material that can be regarded as a source of solid carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon lms have stimulated and diverted the attention of researchers because of their numerous applications such as photovoltaic devices, 1 corrosion inhibition, wear resistant 2 and thermal conductive coatings, 3 chemically inert materials, 4 electroanalysis and sensing devices 5 and regenerative medicine. 6 The efforts, regarding use of carbon lms in biotechnology, can be attributed to their excellent ability to be inert, biocompatible and bioactive with the host.…”
Section: Introductionmentioning
confidence: 99%
“…One of the more popular systems for the so templating synthesis is the FDU-family of mesoporous carbons based on the cooperative assembly of resol and commercial Pluronic non-ionic surfactants, based on poly(ethylene oxide)-block-poly(propylene oxide)-block-poly(ethylene oxide). [15][16][17] Examination of lms for this system has revealed several differences in comparison to the synthesis of bulk powders: the compositional window for the ordered phases can be shied, 11 the morphology can be dependent on the lm thickness, 18 and most strikingly that the ordered structure evolves from disorder on heating through a thermally induced self-assembly (TISA) process. 19 These differences suggest that the best processing conditions for the fabrication in lms and powders will be different, but to date these syntheses have utilized the same long thermopolymerization process (120 C for 24 h) as initially developed to optimize the synthesis of FDU-16.…”
Section: Introductionmentioning
confidence: 99%